Cover Image. (12th August 2018) - Zheng, Yi; Zhang, Ya; Tang, Wenqiao; Guo, Hongyi; Zhu, Yan; Dong, Zhaohui; Jiang, Hui
Abstract : The cover image, by Yi Zheng et al., is based on the Research Article Preliminary in situ teeth study of the narrow‐ridged finless porpoises remains using microsynchrotron radiation X‐ray fluorescence and laser ablation inductively coupled plasma mass spectrometry, https://doi.org/10.1002/xrs.2955 .